Rekayasa Mutu Produksi Gate Valve di P.T. Barindo Anggun Industri - Didik Wahjudi; Amelia Amelia (Institute of Research and Community Outreach, Petra Christian University, 1999)
Casting process in P.T. Barindo Anggun Industri produces many rejected products. This condition will be improved by controlling factors, such as pouring temperature, pouring time, and pouring height. The research shows that those three factors give significant effect and minimum number of rejected products is obtained when pouring temperature is set at 1200°C, pouring time at 10 seconds, and pouring height at 10 centimeters. Abstract in Bahasa Indonesia : Proses pengecoran di P.T. Barindo Anggun Industri menghasilkan banyak produk yang cacat. Keadaan ini akan diperbaiki dengan mengendalikan beberapa faktor, yaitu temperatur penuangan, waktu tuang dan ketinggian cawan tuang. Dari penelitian ketiganya memberikan pengaruh signifikan. Jumlah cacat minimum didapatkan bila temperatur tuang 1200°C, waktu tuang 10 detik, dan ketinggian penuangan 10 cm. Kata kunci : desain eksperimen, rekayasa mutu